A Hybrid Newton-Raphson Unbalanced Three-Phase Loadflow and Rotor’s qd0 Reference Frame of Syncronous Generator Model as An Alternative Tool for Studying The Impact of Unbalanced Loads on Power Angle Change of Three Phase Synchronous Generator Connecte - Kadiman, Sugiarto (ReTII, 2019)
The issues considering power system dynamics are often studied by looking at the dynamic responses of generators connected through the power grid, taking their interactions into consideration. This work decribes a specific study on the impact of unbalanced loads of the grid on rotor angle change of synchronous generators under steady state condition with quantitive evidence. Since the dynamic interactions are usually characterized by both grid-structure-related and status-related variables, an accurate portrait of the dynamic behavior of synchronous generators under unbalanced conditions can be described by a complex nonlinear differential-algebraic model. In this paper, an alternative tool for studying such dynamic behaviour was created by hybrid Newton-Raphson unbalanced three-phase loadflow and rotor’s qd0 reference frame of synchronous generator. Active windows with this generator model based on qd0 framework were developed using Visual’s Graphical User Interface (GUI) capability to examine the rotor angle of the machine after small perturbations, focusing on electromagnetically dynamic as affected by load unbalance. Newton-Raphson unbalanced loadflow was used to derive the generator’s terminal inputs through load-flow analysis on the grid. The results showed that the significant influence of unbalanced loads occured in power angle.